FAKTOR RESIKO PADA KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI RS dr. R. GOETENG TARUNADIBRATA PURBALINGGA - Prasanti Adriani (Universitas Harapan Bangsa Purwokerto, 2017)
Abstract Hospital dr. R. Goeteng Tarunadibrata is one of the largest referral hospitals in Purbalingga District. Data from medical record at dr. R. Goeteng Tarunadibrata obtained infant mortality rate (IMR) in 2014 as many as 109 babies with the incidence of BBLR 41 babies (37.6%), asphyxia 32 infants (29.3%), others 36 babies (33%). In 2015, there were as many as 90 babies with 38 cases of IBBR infants (42.2%), asphyxia 37 infants (41.1%), and 15 infants (16.7%). Based on these data it can be concluded that the highest IMR of 2015-2016 is caused by LBW, although in that year it has decreased but not significant enough. The purpose of this study was to determine the risk factors on the incidence of Weight Loss Low (BBLR) in dr. R. Goeteng Tarunadibrata Purbalingga year 2015-2016. This analytical study uses a case control approach that is used to determine the relationship between the independent variable and the dependent variable. This type of research is a retrospective that seeks to look back, meaning to collect data starting from the effects or effects that have occurred. The national scientific journal is ISSN Viva Medika STIKES Harapan Bangsa Purwokerto. Enrichment of subject matter of neonatal obstetric care in the form of draft. The results of research that has been done in Medical Record Room RSUD dr. R. Goeteng Tarunadibrata Purbalingga about risk factors on the incidence of Low Birth Weight (LBW) in dr. R. Goeteng Tarunadibrata Purbalingga in 2016, it is known that there is a correlation between Mother Age with Low Birth Weight Event (LBW), got p value 0,000. There is a relationship between parity with Low Birth Weight Infant (LBW), obtained p value 0,000. Keywords: Risk factors, LBW, maternal age, parity